Understanding the entrepreneurial mind : opening the black box - Alan L Carsrud (Springer, 2015)
Why do some people start business and others do not? Is entrepreneurship a natural quality or can it be taught? Do entrepreneurs think differently from others? While there is a great deal of literature exploring the dynamics of new firm creation, policies to promote innovation and technology transfer, and the psychology of creativity, research on entrepreneurial mindset or cognition is relatively new, and draws largely from such related fields as organizational behavior, cognitive and social psychology, career development, and consumer research. Over the past fifteen years, the initial model, the theory of reasoned action (TRA), and its successor, known as the theory of planned behavior (TPB), have successfully been applied to entrepreneurship. However, recent findings suggest that considerably more research is required to understand the role of intentions in the entrepreneurial decision process. In this volume, editors Carsrud and Brännback have assembled the most prominent researchers in entrepreneurial psychology to showcase state-of-the-art insights on its many dimensions.